IMPLEMENTASI BUDAYA LITERASI DIGITAL UNTUK MENGUATKAN MODERASI BERAGAMA BAGI SANTRI (STUDI KASUS DI MAHAD UIN MAULANA MALIK IBRAHIM MALANG) - Prastyo, Angga Teguh; Inayati, Isna Nurul (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This study provides a review of the implementation of digital literacy culture to instill the values ??of religious moderation for students in a tertiary-based Islamic boarding school at Mahad UIN Maulana Malik Ibrahim Malang. The focus of the study discusses digital literacy culture at the implementation level and the resulting impact so that it contributes to the formation of more moderate religious thought and behavior for students. The research method is descriptive qualitative. Data collection techniques using interviews, documentation and observation. Meanwhile, data analysis uses flow stages: 1) data reduction, 2) data display, 3) conclusion verification. The findings of this study are to change the mindset of students in a positive way so that they can understand a more moderate Islamic religion. Second, training and building a more connected and trusted social media network between Islamic boarding schools. Third, producing content containing the teachings of religious moderation values ??from Kyai to be distributed in digital media. while the impact resulting from the implementation of digital literacy culture at Mahad UIN Maulana Malik Ibrahim Malang is the emergence of awareness to practice and expand the values ??of religious moderation from Kyai and other religious leaders who are considered to be in harmony with the values ??of Islamic teachings. Second, integrating all values ??of religious moderation in one digital media network so that it is easy for all generations to learn.